Potential advantage of student-run clinics for diversifying a medical school class - Chris N. Gu; Jane A. McElroy; Blake C. Corcoran (Journal of Educational Evaluation for Health Professions, 2012)
The purpose of this study was to evaluate the influence of a student-run clinic on the diversification of a medical student class. We distributed a two-page, 20-item, paper survey to students of the University of Missouri School of Medicine (MU SOM) class of 2015 in July of 2011. The survey gathered information on general demographics, opinions on the importance of medical education opportunities, and opinions on the importance of medical school characteristics in applying to and attending MU SOM. A total of 104 students responded to the survey. A majority of the students identified the MedZou Community Health Clinic, a student-run, free health clinic affiliated with MU SOM, and simulated-patient encounters as important educational experiences (81% and 94%, respectively). More than half of the self-identified “non-white” students reported MedZou as an important factor in their choice to apply to (60%; 95% confidence interval [CI], 32 to 88) and attend (71%; 95% CI, 44 to 98) MU SOM, over half of the females reported MedZou as important in their choice to apply (59%; 95% CI, 43 to 76) and attend (57%; 95% CI, 40 to 74), and over half of non-Missouri residents reported MedZou as important in their choice to apply (64%; 95% CI, 36 to 93) and attend (71%; 95% CI, 44 to 98). According to the above results, it can be said that students clearly value both MedZou and simulated-patient encounters as important educational experiences. Women, minorities, and non-Missouri residents value MedZou more highly than their peers who are First Year Medical Students who are Missouri residents, suggesting that MedZou may provide a promising opportunity to advance diversity within MU SOM. These results highlight the need for additional research to further explore MedZou’s potential to enhance the recruitment of a diverse medical student class.